Boosting Employee Performance Through Collaboration, Communication, and Creative Thinking - Putri, Hayyu Nurabida; Noermijati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this research is to analyze the effects of teamwork, communication, and employee creativity on employee performance. Considered as an explanatory study, it identifies the influence of teamwork, communication, and employee creativity on employee performance using a quantitative approach. From the population of 323 employees of the Regional Office 07 of PT Bank Negara Indonesia (Persero) Tbk in Makassar, 181 were selected as the respondents via probability sampling method and simple random sampling technique. The data analysis was performed using instrument test and multiple linear regression in the Statistical Product and Service Solutions (SPSS) program.